(untitled) (Journal of Tourism and Himalayan Adventures, 2020)
This paper is an attempt to bring forth situations of UV radiation levels or UV index (UVI) and effects affecting different causes to concerned living beings and on environment in the Himalayas. It has analyzed solar radiation data observed at different locations, covering the elevation range of 2735 meters (m) above sea level (a.s.l.) to 4355 m a.s.l of the Nepal Himalayas. In addition, existing research results reported by other researchers on Himalayan UVI and UV guidelines of the World Health Organization (WHO) have been reviewed. The study has identified that mountaineers/ climbers are exposed to enhanced high levels of UV radiation due to the coupled effect of the altitude-related increase of UV radiation and the reflection from snow and ice-covered surfaces. Sun protection measures are essential to be applied according to the UVI range/ categories associated with existing weather conditions and seasons while out climbing or mountaineering, especially during high-intensity sun hours (09:00–13:30 local time (LT)) in the spring and autumn.